A three-level luminescent response in a pyrene/ferrocene rotaxane - Mateo-Alonso, Aurelio; Ehli, Christian; Guldi, Dirk Michael; Prato, Maurizio (Organic Letters, 2013)
A solvent switchable rotaxane equipped with a pyrene stopper and with two ferrocenyl units on the macrocycle is reported, in which three different states, two nondegenerate and one degenerate, can be obtained in different solvents at room temperature. This is accompanied by high contrast changes in fluorescence intensity of the pyrene stopper by the presence of the ferrocenyl moieties on the macrocycle, which quench the emission of pyrene more efficiently with proximity. © 2012 American Chemical Society.